1996
DOI: 10.1136/jmg.33.11.952
|View full text |Cite
|
Sign up to set email alerts
|

Der(22)t(11;22) resulting from a paternal de novo translocation, adjacent 1 segregation, and maternal heterodisomy of chromosome 22.

Abstract: The t(11;22)(q23;qll) translocation is the most frequently identified familial reciprocal translocation in humans. In translocation carriers, 3:1 meiotic segregation with tertiary trisomy can occur resulting in abnormal progeny with the der(22) as the supernumary chromosome. Affected children have a distinct phenotype with multiple anomalies and severe mental retardation. We have identified a child with developmental delay and multiple anomalies consistent with the der(22) phenotype. Cytogenetic analysis showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 17 publications
2
20
0
1
Order By: Relevance
“…For complex sSMC , only one patient with maternal heterodisomy of chromosome 22 has been reported to date in Emanuel syndrome cases (Dawson et al 1996).…”
Section: Ssmc Shapementioning
confidence: 99%
“…For complex sSMC , only one patient with maternal heterodisomy of chromosome 22 has been reported to date in Emanuel syndrome cases (Dawson et al 1996).…”
Section: Ssmc Shapementioning
confidence: 99%
“…She had neonatal diabetes and low birth weight, but no other anomalies and, up to the age at report, developed normally. Dawson et al [16] reported a patient with partial trisomy 1 lq and 22 due to a de novo extra 11 ;22 translocation chromosome. This is the first…”
Section: Upd 16 and Trisomy 16pmentioning
confidence: 99%
“…The single example with a 46,XX,der(22) karyotype, with monosomy for 22q and trisomy for 11q, was found in an early embryonic death resulting in an empty sac (Soler et al, 1993). The other cases produced viable offspring due to subsequent events that rescued the monosomy 22: in one case through a maternal MI nondisjunction of 22 (Dawson et al, 1996), and, in others, most probably by postzygotic nondisjunction involving the der (22) chromosome (Kulharya et al, 2002). Five cases with karyotype 47,t(11;22),+der(22) and phenotype similar to the usual der(22) have been reported (Lockwood et al, 1989;Abeliovich and Carmi, 1990;Lurie and Podelschuk, 1992;Simi et al, 1992;Petkovic et al,1996).…”
Section: Discussionmentioning
confidence: 99%
“…der (22) syndrome Dawson et al (1996) 47,XX/XY,t(11;22)(q23;q11.2)pat, +der (22) ? 2 : 2 alternate + MII or postzygotic nondisjunction of der (22) der (22) Petkovic et al (1996) 46,XX,der (22) …”
unclassified